2007
DOI: 10.1097/sap.0b013e31803bf66c
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Antisense Oligonucleotide Reduces the Expression of Type I Collagen in a Human-Skin Organ-Wound Model

Abstract: Increased collagen expression during wound healing causes scar formation, abnormal contracture, low tensile strength, functional impairment, and disfigurement. A novel ex vivo wound-injury model demonstrated that AS60, an antisense oligonucleotide (ASO) to type I collagen, reduced the mRNA and protein expression of type 1 collagen. Following a cutaneous wound injury in a human-skin organ culture, AS60 injection resulted in a 36% (P < 0.001) and 30% decrease (P < 0.001) in type 1 collagen mRNA and protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recently, the use of human skin explants for evaluating the effect of potential therapeutic agents has been reported. In an attempt to interfere with the fibrotic process, Nath et al recently reported using antisense oligonucleotides to reduce Collagen Type I expression ex vivo in a skin organ culture model that was maintained for 7 days [ 17 ]. To extend the application of human skin explants to in vivo gene therapy, Lippin et al obtained skin explants from patients with chronic renal failure and anemia, injected them with an adenovirus expressing human erythropoietin, and reimplanted them into the patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of human skin explants for evaluating the effect of potential therapeutic agents has been reported. In an attempt to interfere with the fibrotic process, Nath et al recently reported using antisense oligonucleotides to reduce Collagen Type I expression ex vivo in a skin organ culture model that was maintained for 7 days [ 17 ]. To extend the application of human skin explants to in vivo gene therapy, Lippin et al obtained skin explants from patients with chronic renal failure and anemia, injected them with an adenovirus expressing human erythropoietin, and reimplanted them into the patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human HS tissues that satisfied the following requirements were used in the study: 20–50 years; hypertrophic scars had not faded within a year; the patients did not administer any drugs before surgery; confirmation of clinical diagnosis according to the appearance (thickened, raised (>2 mm), red, hard, itchy, and the relevant pathological diagnosis) ( n = 6). Cultured HS tissues ex vivo were performed as described previously [ 24 26 ]. Subcutaneous fat tissues were removed, and HS tissues were cut into 10 × 10 mm sections and cultured with DMEM/80 % ADSC-CM in the presence of a p38 inhibitor (SB203580; 10 μM) and activator (anisomycin; 25 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Lowering collagen expression in these tissues may have implications in improving their mechanical properties during the healing process of ligaments and tendons. Our own study demonstrated the efficacy of directly targeting the COL1A1 collagen gene using antisense to type 1 collagen, reducing collagen expression in a human-skin organ model [20].…”
Section: Discussionmentioning
confidence: 79%
“…Hence there is a critical need for effective and safe therapies. We have previously demonstrated that the type 1 collagen antisense oligodeoxynucleotide, AS60-ODN (a human analog of mouse AS61-ODN) reduced the mRNA and protein expression of type 1 collagen in a novel ex vivo human wound injury model [20] .…”
Section: Introductionmentioning
confidence: 99%